The adhesiveness of native platelets and its prevention - O'Brien, J. R. (1961)
The following methods were used to measure the adhesion to various surfaces of platelets in whole blood or plasma: 1, two measurements gave an estimate in vivo of platelet adhesion to cut human capillaries; 2, platelets adhering to damaged cells in vitro were counted directly; 3, a highly reproducible method for estimating platelet adhesion to glass was devised; 4, the manner in which platelets adhere to each other (aggregation) was also studied. Platelet adhesion to all these surfaces was found to be dependent upon calcium and independent of all clotting factors except that platelet aggregation is probably dependent upon thrombin. A number of drugs—mostly antimalarials, antihistaminics, and local anaesthetics—in suitable concentration inhibited adhesion. They probably form a fixed, orientated layer on glass and possibly on cells and make these surfaces unattractive to a platelet. They also stick reversibly to live cells (including platelets) altering their permeability, and they may make platelets less adhesive. Consequently the possibility of using antiadhesive drugs therapeutically to inhibit thrombus formation was considered.